Biomechanics of transapical mitral valve implantation - Koenig, Evan Kienholz, author; Dasi, Lakshmi Prasad, advisor; Prasad, Ashok, committee member; Orton, Christopher, committee member (Colorado State University. Libraries, 2014)
Heart disease is the number one killer in the United States. Within this sector, valve disease plays a very important role: Approximately 6% of the entire population has either prolapse or stenosis of the mitral valve and this percentage only increases when looking only at the elderly population. Transapical mitral valve implantation has promised to be a potential therapy for high-risk patients presenting with MR; however it is unclear what the best method of securing a valve within the mitral annulus may be to provide a safe and efficient valve replacement. The objective of this research is to study and understand the underlying biomechanics of fixation of transapical mitral valves within the native mitral annulus. Two different transapical mitral valve prosthesis designs were tested: One valve design has a portion of the leaflets atrialized such that it has a shorter stent height and the valve itself sits within the native annulus, the other design is not atrialized and protrudes further into the left ventricle. The valves were implanted in a left heart simulator to assess leaflet kinematics and hemodynamics using high speed imagery and particle image velocimetry techniques. An in vitro passive beating heart model was then used to assess the two different fixation methods (namely, anchored at the apex vs. anchored at the annulus) with respect to paravalvular regurgitation. Leaflet kinematics and hemodynamics revealed proper leaflet coaptation and acceptable pressure gradients and inflow fillings; however, both designs yielded elevated turbulence stresses within the ventricle. At 60 beats per minute, leaflet opening and closing times were both under 0.1 seconds, max Reynolds shear stresses were between 40 and 60 N/m2 and maximum velocities were approximately 1.4 m/s. Assessment of the different fixation methods during implantation revealed the superiority of the atrialized valve when anchored at the annulus (p<0.05), but showed no such comparison during tethered implantation. In addition to the results of statistical testing, observations show that the importance of the relationship between ventricular stent height and fixation method compared with native anatomy plays an important role in overall prosthesis function regardless of implantation method.